GSK3 is a negative regulator of the thermogenic program in brown adipocytes - Markussen, Lasse K. (Sci Rep, 2018)
Brown adipose tissue is a promising therapeutic target in metabolic disorders due to its ability to dissipate energy and improve systemic insulin sensitivity and glucose homeostasis. β-Adrenergic stimulation of brown adipocytes leads to an increase in oxygen consumption and induction of a thermogenic gene program that includes uncoupling protein 1 (Ucp1) and fibroblast growth factor 21 (Fgf21). In kinase inhibitor screens, we have identified glycogen synthase kinase 3 (GSK3) as a negative regulator of basal and β-adrenergically stimulated Fgf21 expression in cultured brown adipocytes. In addition, inhibition of GSK3 also caused increased Ucp1 expression and oxygen consumption. β-Adrenergic stimulation triggered an inhibitory phosphorylation of GSK3 in a protein kinase A (PKA)-dependent manner. Mechanistically, inhibition of GSK3 activated the mitogen activated protein kinase (MAPK) kinase 3/6-p38 MAPK-activating transcription factor 2 signaling module. In summary, our data describe GSK3 as a novel negative regulator of β-adrenergic signaling in brown adipocytes.